A extensão universitária como práxis educativa do bacharel em direito da Universidade Federal do Pará: o caso do Núcleo de Assessoria Jurídica Universitária Popular Aldeia Kayapó (2004-2014) - GOMES, Raphael Carmesin (Universidade Federal do Pará, 2019)
This research aims to identify what the function of the University Extension to degree of UFPA’s Bachelor of Law, having as a case study the Núcleo de Assessoria Jurídica Universitária Popular “Aldeia Kayapó” (NAJUPAK). To achieving it, we describe, briefly, the pattern of universitary institution, principally of the University Extension to verify what kind of university extension was contitute historically into the degree of UFPA’S Bachelor of Law. Then, we analyse the extension activity of Bachelor of Law as praxis, to explore the praxis of NAJUPAK. The procedure to gather datas is based in the documental research, principally books and papers that support at the path of dissertation, in the official documents that rule de University Extension (laws, management reports, etc.), in analysis of extension program selected. The research is based also in interviews made with subjects that belong to NAJUPAK during their degrees. This datas are confronted with theoretical background and with datas collected documentally. We see that NAJUPAK was a counterpoint in relation to formation at UFPA’s Law. While the “official” curriculum is constitute by stanch juridical disciplines of positivism, the NAJUPAK allowed to Bachelors unique educative experiences, evoking subjects, authors and methodologies of teaching.